2019
DOI: 10.1029/2018jc014391
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐Up of the Southern Hemisphere Super Gyre

Abstract: This study investigates the variability of the Southern Hemisphere super gyre (SHSG), using remotely sensed altimeter measurements, in situ Argo observations, and results from an ocean state estimate of the Consortium for Estimating the Circulation and Climate of the Ocean. Analyses of altimeter data show large trends of sea surface height, and their positive-negative contrast suggests a strengthening of subtropical gyres in all the three Southern Hemisphere oceans since 1993. Analyses of Argo data and the Est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 81 publications
(153 reference statements)
7
64
2
Order By: Relevance
“…Nearly 70% of the observed increase in the total SAMW volume between 2005 and 2015 can be accounted for by the increasing SAMW subduction rates. Enhanced westerly winds associated with an increasing SAM directly contribute to the deepening of the MLDs, the strengthening of the subtropical gyres (Qu et al, 2019;Ridgway & Dunn, 2007;Roemmich, 2007), the increasing of the SAMW subduction rates, and eventually the warming of the subsurface layers in the extratropical Southern Hemisphere ocean. downloaded at http://apdrc.soest.hawaii.edu/ website, and the NCEP Reanalysis wind product was downloaded at https://www.esrl.noaa.gov/psd/data/gridded/data.ncep.reanalysis.surfaceflux.html/ website.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 70% of the observed increase in the total SAMW volume between 2005 and 2015 can be accounted for by the increasing SAMW subduction rates. Enhanced westerly winds associated with an increasing SAM directly contribute to the deepening of the MLDs, the strengthening of the subtropical gyres (Qu et al, 2019;Ridgway & Dunn, 2007;Roemmich, 2007), the increasing of the SAMW subduction rates, and eventually the warming of the subsurface layers in the extratropical Southern Hemisphere ocean. downloaded at http://apdrc.soest.hawaii.edu/ website, and the NCEP Reanalysis wind product was downloaded at https://www.esrl.noaa.gov/psd/data/gridded/data.ncep.reanalysis.surfaceflux.html/ website.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies that investigated changes in the subtropical gyres under climate change also emphasized changes in WBCs. All WBCs (except the Gulf Stream) are expected to intensify and to shift poleward (Yang et al 2016(Yang et al , 2020Qu et al 2019), with a larger warming trend over the WBCs than globally (Wu et al 2012). G. suggested that an increase in the stratification (Luo et al 2018) strengthens the barrier between the upper and lower circulation due to the baroclinic nature of the gyres, and thereby results in acceleration at near surface and slowdown in the lower thermocline.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements and monitoring of the TL are difficult because the TL involves oceanic eddies and filaments. A recent study showed that the TL may carry as much as 10 Sv of Pacific water to the Indian Ocean (Qu et al 2019). TL variations on various timescales and their relationships with climate variability need to be studied.…”
Section: Tasman Leakagementioning
confidence: 99%